Identification of Multiple Soluble Fe(III) Reductases in Gram-Positive Thermophilic Bacterium Thermoanaerobacter indiensis BSB-33 - Subrata Pal (International Journal of Genomics)
Thermoanaerobacter indiensis BSB-33 has been earlier shown to reduce Fe(III) and Cr(VI) anaerobically at 60°C optimally. Further, the Gram-positive thermophilic bacterium contains Cr(VI) reduction activity in both the membrane and cytoplasm. The soluble fraction prepared from T. indiensis cells grown at 60°C was found to contain the majority of Fe(III) reduction activity of the microorganism and produced four distinct bands in nondenaturing Fe(III) reductase activity gel. Proteins from each of these bands were partially purified by chromatography and identified by mass spectrometry (MS) with the help of T. indiensis proteome sequences. Two paralogous dihydrolipoamide dehydrogenases (LPDs), thioredoxin reductase (Trx), NADP(H)-nitrite reductase (Ntr), and thioredoxin disulfide reductase (Tdr) were determined to be responsible for Fe(III) reductase activity. Amino acid sequence and three-dimensional (3D) structural similarity analyses of the T. indiensis Fe(III) reductases were carried out with Cr(VI) reducing proteins from other bacteria. The two LPDs and Tdr showed very significant sequence and structural identity, respectively, with Cr(VI) reducing dihydrolipoamide dehydrogenase from Thermus scotoductus and thioredoxin disulfide reductase from Desulfovibrio desulfuricans. It appears that in addition to their iron reducing activity T. indiensis LPDs and Tdr are possibly involved in Cr(VI) reduction as well.